Options for women to become legislative candidates for political parties - Moerti Hadiati (University of Merdeka Malang, 2005)
Opportunities for women who are involved in politics are wide open. However, in reality, these opportunities have not been used optimally. Evidently, there are still a few women who become members of the People's Representative Council (DPR). This study aims to determine the reasons for women running as legislative candidates. In addition, it is also investigated how the efforts of political parties in preparing their party members to become legislative candidates.